HUBUNGAN WAKTU BELAJAR DI LUAR JAM SEKOLAH DENGAN HASIL BELAJAR FISIKA DI SMA NEGERI 2 MATARAM - Afifah, Gusti; Ayub, Syahrial; Ardhuha, Jannatin; Verawati, NNSP (Universitas Hamzanwadi, 2020)
This research aims to obtain a picture of study time outside school hours with the physics learning outcomes of students of SMA Negeri 2 Mataram. This type of research is a descriptive study by interpreting the data as it is. Learning time data collection outside of school hours is obtained through a questionnaire or card that is filled in every day as students study the subject of waves and optics. Data on physics learning outcomes are obtained by multiple choice tests. The data is processed by the product moment correlation formula, followed by a test of the significance of the correlation coefficient. Data analysis conducted there was a significant relationship between study time outside school hours with physics learning outcomes of students of SMA N 2 Mataram with rhitung = 0.96 and rtabel = 0.32 for a significance level of 5%. The percentage of study time outside of school hours independently is greater than in a guided manner